National healthcare expenditure influences CRT implantations- results from CRT Survey II with 11088 patients. (25th November 2020) - Normand, C; Linde, C; Bogale, N; Dickstein, K
Abstract: Background: Cardiac Resynchronization Therapy (CRT) reduces morbidity and mortality in selected patients with heart failure (HF) and electrical dyssynchrony. This treatment receives level I recommendations in ESC guidelines from both HFA and EHRA. However, despite these strong recommendations, CRT implantation practice varies greatly in ESC member states. Purpose: To describe how countries' healthcare expenditure affects CRT implantation practice. Methods: Between 2015 and 2017, two ESC associations, EHRA and HFA, conducted the CRT Survey II, a survey of CRT implantations in 11, 088 patients in 42 ESC member states. We divided these countries into three groups according to their current health expenditure per capita. Results: The countries with the lowest health care expenditure were more likely to implant CRT in patients who had strong guideline recommendations for implantation such as symptomatic heart failure, LVEF≤35%, sinus rhythm, QRS duration ≥150 ms and LBBB. These countries were also less likely to implant patients with weaker recommendation level such as those with atrial fibrillation, and were more likely to implant CRT in patients hospitalized for HF in the past year or with NYHA functional class III or IV HF. Conclusions: CRT Survey II has demonstrated a non-uniform delivery of healthcare. Countries with low health care expenditure appear to be reserving CRT therapy for younger patients, those with guideline recommendation level I indications and patients with more severe symptoms of heart failure. Funding Acknowledgement: Type of funding source: Other. Main funding source(s): The work was supported by the European Heart Rhythm Association; the Heart Failure Association; Biotronik; Boston Scientific; Medtronic; Sorin; St. Jude; Abbott; Bayer; Bristol-Myers Squibb and Servier.